2020
DOI: 10.3390/electronics9081195
|View full text |Cite
|
Sign up to set email alerts
|

Security in Low Powered Wide Area Networks: Opportunities for Software Defined Network-Supported Solutions

Abstract: The Internet of things (IoT) has revolutionized the use of connectivity and has given birth to new transmission technologies to satisfy the requirements of diverse IoT applications. Low powered wide area networks (LPWAN) is one of those transmission technologies, and is becoming exceptionally useful for IoT applications. The nodes use energy-efficient mechanisms for long-range data transmission (10–20 km), lasting in hostile environments for years and making them suitable for IoT applications such as environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 105 publications
0
13
0
Order By: Relevance
“…Various studies use flexible time division multiple access (TDMA) as the most suitable that decreases interference and decreases power consuming. In [ 25 ], the author details more interference techniques in WBAN. Table 3 includes a summarization of some selected studies according to the used sensors, collected data, and the transmission protocols.…”
Section: Main Components Of the Rpm Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies use flexible time division multiple access (TDMA) as the most suitable that decreases interference and decreases power consuming. In [ 25 ], the author details more interference techniques in WBAN. Table 3 includes a summarization of some selected studies according to the used sensors, collected data, and the transmission protocols.…”
Section: Main Components Of the Rpm Systemmentioning
confidence: 99%
“…Table 3 showed a description of the collected articles according to various factors include (Diseases, collected data, the sensor used and the transmission protocol). The authors of [25], provide a comprehensive survey about security and privacy among WS devices. Interoperability and integration: Health data are usually big and heterogeneous; therefore, interoperability is a critical issue.…”
Section: Wban Challenges In Rmsmentioning
confidence: 99%
“…Intrainterference is the most common in a single WBAN. Numerous studies have shown that flexibility time division multiple access (TDMA) is the best option for reducing interference and power consumption [19].…”
Section: Notification Componentsmentioning
confidence: 99%
“…Overall, various survey-based studies highlighting the vulnerabilities in LPWAN communication technologies have identified an urgent need for secure and uninterrupted communication between an end-device and the gateway for secure and effective IoT networks for large-scale IoT deployments. While there is greater potential in the emergence of software-defined network (SDN) architecture for security in IoT, the protocols in SDN are still under development [37,38].…”
Section: Related Work and Research Contributionmentioning
confidence: 99%